2020
DOI: 10.1093/mnras/staa3559
|View full text |Cite
|
Sign up to set email alerts
|

Modelling X-ray RMS spectra II: the ultrafast outflow of PDS 456

Abstract: We present an improved model for excess variance spectra describing ultra-fast outflows and successfully apply it to the luminous (Lbol ∼ 1047erg s−1) low-redshift (z = 0.184) quasar PDS 456. The model is able to account well for the broadening of the spike-like features of these outflows in the excess variance spectrum of PDS 456, by considering two effects: a correlation between the outflow velocity and the logarithmic X-ray flux and intrinsic Doppler broadening with vint = 104 km s−1. The models were genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…This means that it is likely very degenerate with other parameters that have the same function, in this case the UFO ionisation/powerlaw flux correlation parameter 𝑐 UFO . The value of 𝑐 UFO here is 0.2-0.3, which is much lower than the values of 0.6 found in IRAS 13224-3809 (Parker et al 2020) and 0.5-1 in PDS 456 (Härer et al 2021). Secondly, we note that the Fe UFO line is much stronger here than in the other two sources.…”
Section: High Flux Average 𝐹 Var Spectrumcontrasting
confidence: 71%
See 1 more Smart Citation
“…This means that it is likely very degenerate with other parameters that have the same function, in this case the UFO ionisation/powerlaw flux correlation parameter 𝑐 UFO . The value of 𝑐 UFO here is 0.2-0.3, which is much lower than the values of 0.6 found in IRAS 13224-3809 (Parker et al 2020) and 0.5-1 in PDS 456 (Härer et al 2021). Secondly, we note that the Fe UFO line is much stronger here than in the other two sources.…”
Section: High Flux Average 𝐹 Var Spectrumcontrasting
confidence: 71%
“…We note in Section 4.1 that the UFO variance in 1H 0707-495 is significantly stronger than that observed in IRAS 13224-3809 and PDS 456 (Parker et al 2020;Härer et al 2021). The reason for this is not clear, but the relatively low value of the ionization correlation 𝑐 UFO suggests that it is not being driven by the UFO gas responding to the continuum.…”
Section: The Ultra-fast Outflowmentioning
confidence: 81%
“…In Parker et al (2017) and Pinto et al (2018) we showed that the absorption lines from the UFO in IRAS 13224-3809 respond to the X-ray continuum, weakening as the flux rises in a manner consistent with ionisation of the gas. This has also been observed in PDS 456 (Parker et al 2018a;Härer et al 2021), 1H 0707-495 (Parker et al 2021;Xu et al 2021), and 30-60% of a sample of variable AGN observed with XMM-Newton (Igo et al 2020), suggesting it is a general property of UFOs. If the ionisation interpretation of these observations is correct, then a similar effect may be visible in the emission from winds.…”
Section: Ionisation Changesmentioning
confidence: 52%
“…PDS 456 is a low redshift (𝑧 = 0.184) radio quiet quasar, which hosts one of the earliest detected UFOs (Reeves et al 2003) and has clear evidence for multiple layers of absorption (Reeves et al 2016(Reeves et al , 2018Härer et al 2021). As well as the absorption, a strong, broad Fe emission line is present from ∼ 6-8 keV (rest frame).…”
Section: Pds 456mentioning
confidence: 99%
“…As two individual samples, PDS 465 and PG 1211+143 are often referenced in previous works (e.g. Pounds et al 2003;2016;Reevies et al 2009;Härer et al 2021;Danehkar et al 2018). PDS 456, a radio-quiet quasar with a bolometric luminosity L bol ∼ 10 47 erg/s, was measured to show the UFOs launched with ∼50r s (Reevies et al 2009).…”
Section: Application To Ufosmentioning
confidence: 99%